Study of Gurney Flap as Passive Flow Control Method on NACA 4418 - Abhitah, Athallah Nabiel; Rhakasywi, Damora; Fahrudin, Fahrudin (Journal La Multiapp, 2024)
Global problems related to the greenhouse effect and global warming have pushed research towards clean energy sources. One of the technologies of concern is wind turbines, whose performance is highly dependent on the aerodynamics of the airfoils used. This study aims to analyze the effect of input speed variation on the aerodynamic performance of NACA 4418 airfoil using gurney flap as a passive flow method. In this study, the Reynolds Averaged Navier-Stokes (RANS) method was used to calculate aerodynamic parameters, by varying the height of the gurney flap on the trailing edge of the airfoil. The results showed that the use of gurney flaps with flap height variations of 1%, 2%, and 3% of chord length was able to significantly increase the lift coefficient, with the highest increase at the flap height of 3% c. In addition, this passive method has proven to be efficient in improving aerodynamic performance without the addition of an active control system. In conclusion, variations in input speed and flap height can improve the aerodynamic performance of NACA 4418 airfoils, making this method feasible to apply to wind turbines.